A robust control for a variable wind speed conversion system energy based on a DFIG using Backstepping. Issue 1 (February 2023) - Jenkal, Hasnaa; Lamnadi, Mouna; Mensou, Sara; Bossoufi, Badre; Boulezhar, Abdelkader
This paper presents a modeling and robust control of the DFIG (doubly fed induction generator) used in the wind energy conversion system (WECS). We started by using the MPPT method to extract the maximum power in the WECS, modeling the double-fed inductor generator, and then applying the Backstepping controller to control the reactive power and electromagnetic torque in order to test the performance and the robustness of the system. All is simulated and presented in MATLAB/SIMULINK software.